KETAHANAN EKONOMI MASYARAKAT CICERI JAYA DI MASA PANDEMI COVID-19 : STUDI KAMPUNG SANTRI UIN SMH BANTEN - Wawan Wahyudin; Itang Itang (LPPM Universitas Bina Bangsa, 2024)
This study discusses the impact and changes that have occurred on the resilience method of community economic empowerment during the Covid-19 pandemic. As we all know, at the end of 2019, the world was worried by a disease called Corona or Covid-19. Even though almost all sectors are affected by Covid-19, community economic activities must still be carried out, including other resilience sectors, namely community economic empowerment. The research method used in this study is by using a descriptive research method with a qualitative approach that emphasizes the analysis of the dynamics of the relationship between the observed phenomena, using scientific logic. Some of the findings resulting from this study are that the impact of Covid-19 on economic resilience and empowerment is giving birth to a new method, namely the online entrepreneurship method. Likewise, in the empowerment of the sharia economy, there is an impact of the same change, that as an alternative method of muamalah practice which was originally directly changed to an online system